Modernization Of Islamic Religious Education in The Era of Society 5.0 - Zikril Hakim; Sherly Yanti; Mukmin (Chalim Journal of Teaching and Learning, 2025)
This study aims to analyze the modernization of PAI in the context of Society 5.0 through a literature study approach with thematic analysis of the current literature. The Society 5.0 era brought fundamental changes in the world of education, including Islamic Religious Education (PAI), which historically often used conventional lecture-based learning approaches. Technological transformation that integrates artificial intelligence, big data, the internet of things, and digital analytics demands religious learning that not only emphasizes information transmission, but also builds critical, collaborative, creative, and technologically literate competencies. The results of the study show that the modernization of PAI learning requires a pedagogical reconstruction that leads to a participatory, digital-interactive, and student-centered model. In addition, modernization also depends on teacher readiness, support for digital facilities, curriculum flexibility, and classroom culture that encourages collaboration. The research concludes that PAI learning must move from a textual paradigm to an integrative approach that combines Islamic values with 21st century competencies in order to be able to respond to the moral, social, and technological challenges of the modern generation. This modernization is a strategic foundation in strengthening the religious character as well as the adaptive abilities of students in the midst of accelerating digital transformation.